The world wide web featuring Microsoft Internet Explorer 4 - Barker, Donald I. (Illustrated series., 1998)
Master the basics of Windows software quickly and easily with the Illustrated Series from Course Technology. Each Illustrated text is designed to be like Windows itself: graphical, intuitive, accessible. The highly visual page design combines large, easy-to-read text, step-by-step instructions, oversized screen illustrations, and reference material to give you an interactive learning experience.